Vous êtes sur la page 1sur 97

 

 

 

 

 

 

 

 

f 0 = 1 [ ]

x 1 (t) =

x 2 (t) = 4 + 1.8 · cos 2 · π · f 0 · t + π + 0.8 · sin (6 · π · f 0 · t)

6 2 · cos (2 · π · f 0 · t) + 3 · sin (2 · π · f 0 · t)

3

x 1 (t) x 2 (t)

x 1 (t) = 6 2 · cos (2 · π · f 0 · t) + 3 · sin (2 · π · f 0 · t) x 1 (t)

x (t) = a 0

2

+

k=1

a k · cos (2 · π · k · f 0 · t) +

k=1

b k · sin (2 · π · k · f 0 · t)

a 0

2

=

12

2

= 6

f 0 b 1 = 3

=

1 [ ]

a 1

=

2

k

A

10

8

6

4

2

6

4

2

0

k A α k / π 10 8 6 4 2 6 4 2 0 Signal

0

0.5

1

1.5

4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps
4 2 6 4 2 0 Signal temporel 0 0.5 1 1.5 Spectre unilatéral 2 temps

2

2.5

3

3.5

4

x 10 3

6 4 2 0
6
4
2
0
6 4 2 0
0 1000 2000 3000 4000 5000 −5000 0 5000 k f 0 k f 0
0 1000
2000
3000
4000
5000
−5000
0
5000
k f 0
k
f 0
1
1
0.5
0.5
0
0
−0.5
−0.5
−1
0 1000
2000
3000
4000
5000
−5000 −1
0
5000
k f 0
k f 0
f_ex_SF_1_1_1.eps
/X(jk) / π

x 1 (t)

A 0 = a 0

2

= 12

2

= 6

A 1 = a 2 + b 2 = (2) 2 + 3 2 = 3.6056

1

1

α 1 = arctan b 1 = arctan 3 = 2.1588 [ ] = 123.6901 [ ]

a

1

2

x 1 (t) =

6 2 · cos (2 · π · f 0 · t) + 3 · sin (2 · π · f 0 · t)

=

A 0 + A 1 · cos (2 · π · f 0 · t + α 1 )

=

6 + 3.6056 · cos (2 · π · f 0 · t 2.1588)

x 2 (t) = 4 + 1.8 · cos 2 · π · f 0 · t + π + 0.8 · sin (6 · π · f 0 · t) x 2 (t)

3

a 0

2

= 8 = 4

2

f 0

a 3 = 0 b 3 = 0.8

=

1 [ ]

3 · f 0

=

3 [ ]

a 1

b 1

A 0 = a 0 = 4

2

A 1 = 1.8

α 1 = π

3

= a 2 + b 2

1

1

A 3 = a 3 + b 3 = 0 2 + 0.8 2 = 0.8

2

2

α 3 = arctan b 3 = arctan 0.8 → − π

2

a

3

0

x 2 (t) =

4 + 1.8 · cos 2 · π · f 0 · t + π + 0.8 · sin (6 · π · f 0 · t)

3

= 4 + 1.8 · cos 2 · π · f 0 · t +

= A 0 + A 1 · cos (2 · π · f 0 · t + α 1 ) + A 3 · cos (6 · π · f 0 · t + α 3 )

π

3

+ 0.8 · cos 6 · π ·